Foot Print of Macro Fungi in The Coastal Forest of Bama, Baluran National Park, East Java - Sri Rahayu; Annisa Wulan Agus Utami; Cahyo Nugroho; Endah Yuliawati Permata Sari; Kusuma Wardani Lydia Puspita Sari; Maghfirah Idzati Aulia; Noor Adryan Ilsan (Universitas Islam Negeri Mataram, 2020)
Baluran National Park, West Java, as one of the conservation sites in Indonesia, has the attraction of the varied types of ecosystems, including fungi. This study aimed to analyze the diversity of fungi in Bama Coastal Forest, Baluran National Park. The method was explorative with plot purposive sampling technique. Parameters in this study include abundance, dominance, and diversity of fungi enriched with physical parameters of humidity and temperature. The fungi were documented and macroscopically observed. Data were analyzed using the abundance index, dominance index, and diversity index. This research identified 18 types of macrofungi in Bama Coastal forest, Baluran National Park East Java including Ganoderma, sp, Hexagonia tenuis, Trametes hirsute, Phellinus sp.1 and sp.2, Ganoderma applanatum, Phellinus igniarius, Pycnoporus cinnabarinus, Daedalea quercina, Tyromyces chioneus, Microporus xanthopus, Calvatia sp., Irpex lacteus, Trichaptum sp., Lentinus sp. Poria corticola, Tyromyces sp., and Lichemomphalia sp. One fungi species (Ganoderma sp.) has the highest abundance index (27.62). The Medium abundance index was found in three species (Hexagonia tenuis, Tyromyces chioneus, Tyromyces sp.) while the rest fungi were in low abundance index. Dominance index of all fungi species identified in Bama was in low category (D<0.5) with medium diversity (2.30). It can be concluded that the diversity of microfungi in the coastal forest of Bama, Baluran National park was a distribution medium of individual of each species and medium community stability. Environmental conditions in the Bama Coast Forest with 93% humidity and an average air temperature of 26-27oC could support for the fungi to grow quite well.